Use of telbivudine in kidney transplant recipients with chronic hepatitis B virus infection: A preliminary experience. Issue 5 (May 2016) - Yap, Desmond Y. H.; Chan, Tak Mao
Abstract: Telbivudine is a relatively novel oral nucleoside analogue with favourable efficacy and tolerability in treatment‐naïve chronic hepatitis B virus (HBV) infection, but its data in kidney transplant recipients (KTRs) was lacking. The efficacy and tolerability of telbivudine in four treatment‐naïve HBsAg‐positive KTRs were reviewed (treatment duration 54 (36–72) months) HBV DNA declined from 2.6 × 10 5 (7.8 × 10 3 –1.5 × 10 7 ) copies/mL at baseline to 170 (0.0–3.2 × 10 4 ) copies/mL at 12 months, and became undetectable at 24 and 36 months ( P = 0.060, 0.118 and 0.005 compared with baseline). Alanine aminotransferase levels dropped from 46.5 (30–48) IU/mL at baseline to 28 (13–45) IU/mL, 34.5 (15–71) IU/mL and 26 (12–41) IU/mL at 12, 24 and 36 months, respectively ( P = 0.109, 0.715 and 0.068 compared with baseline). Serum creatinine level and estimated glomerular filtration rate (eGFR) remained stable after 36 months of treatment ( P all > 0.05 compared with baseline). No virological breakthrough, cirrhosis or hepatocellular carcinoma occurred. Our pilot data suggests that telbivudine has favourable efficacy and renal safety profiles in HBsAg‐positive KTRs.